A green process for the conversion of hazardous sintering dust into K2SO4 and NH4Cl fertilizers. (15th January 2023) - Wang, Qiren; Ma, Xin; Wang, Shuai; Cao, Zhanfang; Hua, Zongwei; Zhong, Hong
Abstract: Sintering dust from the steelmaking industry is a hazardous waste that is rich in valuable metals. The purpose with the present study has been to design an efficient process for the preparation of K2 SO4 and NH4 Cl fertilizers by using sintering dust as raw material. The K, S, and Cl in the sintering dust were selectively and efficiently leached using water. The leaching of Ca impurities was then greatly reduced and the appearance of Zn and Mg was avoided. The Cl − ions in the leachate were, thereafter, adsorbed by a 201 × 7 resin to form a K2 SO4 solution. Finally, the loaded Cl − on the resin was desorbed to form a NH4 Cl solution, and the resin was regenerated and recycled. The purified solutions were crystallized to prepare K2 SO4 (s) and NH4 Cl(s) products, which met the national standard of China for superior potassium sulfate and ammonium chloride, to be used for agricultural use. The recoveries of K, Cl, and S from the sintering dust were 80.78%, 92.63%, and 93.92%, respectively. Notably, the Mn content in the leaching residue increased from 9.08% to 14.19%. This could be used for the conversion of Mn impurities into recyclable manganese-rich raw materials. This green process enables an effective extraction of important impurities in hazardous sintering dust, thereby providing a new potassium source for potash fertilizer manufacturing with notable economic and environmental benefits. Graphical abstract: K2 SO4 and NH4 Cl prepared from recycling of sintering dust: From hazardous solid waste to fertilizers. Image 1 Highlights: A novel process was proposed to prepare fertilizers using sintering dust. The high selective recovery of K, S, and Cl can be achieved by water leaching. The separation of K, S, and Cl is achieved by ion exchange using the 201 × 7 resin. K, Cl, and S in the leachate have been used to prepare two high-quality fertilizers. The leaching residue can be converted into recyclable manganese-rich raw materials.